Analisa Yuridis Eksekusi Sita Jaminan Terhadap Tindak Pidana Pencucian Uang (TPPU) First Travel - Edward Fernando Siregar; Helvis Helvis; Markoni Markoni (Jurnal Syntax Transformation, 2021)
Law No. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering (hereinafter referred to as the “AML Law”) does not specifically regulate assets (assets) resulting from money laundering. where victims must submit to court decisions that have permanent legal force. In the case of PT. First Karya Wisata (FIRST TRAVEL) as stated in Supreme Court Decision No: 3096K/PID.SUS/2018 Jo. 195/PID/2018/PT.BDG Jo. 83/PID.B/2018/PN.DPK), the background of the writing is because there were 63,310 prospective Umrah pilgrims who were not dispatched by the convicts as FIRST TRAVEL, with an Umrah package worth Rp. 14.300.000 and therefore the author intends to analyze the qualifications of the criminal acts of the convicts and the execution of the confiscation of the proceeds of the crime of money laundering offences. The author uses normative research methods. The data used is secondary data supported by primary data, secondary data obtained from library materials. The type of approach used is the law and case approach. Based on the results of research conducted by the author, it is known that criminal acts committed by the convicts can be qualified as criminal acts of fraud, embezzlement and money laundering. Where in the decision of the Supreme Court Number: 3096K/PID.SUS/2018 Jo. 195/PID/2018/PT.BDG Jo. 83/PID.B/2018/PN.DPK which has permanent legal force, assets are confiscated by the state, causing injustice to the victims of prospective Umrah pilgrims considering that the proceeds of the crime were obtained from the personal property of the victims so that in fact the state did not suffer losses, in In this case, the author argues that with the current progress of social media, victims can make petitions on social media so that there is a new way of returning assets from money laundering offences for victims